Atrial Fibrillation Burden Detected by Dual-Chamber Pacemakers as a Predictor for Cardiac Outcomes: A Retrospective Single-Center Cohort Study - Chu, Song-Yun; Jiang, Jie; Wang, Yu-Ling; Sheng, Qin-Hui; Zhou, Jing; Ding, Yan-Sheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) might lead to adverse cardiac consequences. The association between AF burden and cardiac prognosis is unknown. Methods and Results: This retrospective cohort study enrolled 204 patients (117 males; age 74.5 ± 11.5 years) who underwent dual-chamber pacemaker implantation in our center from October 2003 to May 2017. During a median follow-up of 66.5 months, AF could be detected in 153 (75%) of the 204 pacemaker patients. Primary endpoint events (composite cardiac readmission, stroke or systemic embolism, and all-cause death) occurred in 83 cases (40.7%). In logistic regression analysis, AF detection was associated with increased risks of composite endpoints [odds ratio (OR) = 2.9, 95% confidence interval (CI): 1.3–6.2, p = 0.007], and the hazard was mainly driven by increased cardiac readmission (OR = 2.2, 95% CI: 1.1–4.7, p = 0.034). No significantly elevated risk for new-onset stroke, systemic embolism, or deaths were found in patients with AF detected than those without AF recorded. AF duration grade of more than 6 min suggested progressively increased composite endpoints (OR = 1.8, 95% CI: 1.2–2.7, p for trend = 0.005), cardiac readmission (OR = 1.8, 95% CI: 1.2–2.7, p for trend = 0.005), especially heart failure or acute coronary syndrome-associated readmission (OR = 1.8, 95% CI: 1.2–2.9, p for trend = 0.010), than those with shorter (<6 min) or no AF episodes. Kaplan–Meier analyses and Cox regression also suggested that episodes of AF more than 6 min predicted future cardiac events. Conclusions: AF detected by pacemakers were common. Higher AF burden predicted more adverse cardiac outcomes and might suggest the intervention of rhythm control in these population.